Legal Protection Against The Exploitation of Child Labor in Indonesia - Siti Maymanatun Nisa (Asian Journal of Law and Humanity, 2021)
This paper discusses the causes and impacts of exploitation of child labour in Indonesia, protection and legal sanctions for perpetrators of exploitation of child labour in Indonesia. This normative juridical research uses a statutory, conceptual and case approach. The analysis technique uses prescriptive analysis with logic and legal reasoning. The results of the study indicate that the cause of child labour exploitation is poverty; low education of parents and children; social environment; and culture. The impacts of child labour exploitation include: a) not having time to play b) children's growth and development, poor physical and mental health of children c) low self-esteem; d) Vulnerable to discriminatory treatment and work accidents; e) vulnerable to acts of violence, exploitation and abuse. Legal protection for exploited children is carried out by 1) disseminating relevant laws and regulations; 2) monitoring, reporting, and providing witnesses, and; 3) involvement of companies, trade unions, non-governmental organizations, and the community. Sanctions against the exploitation of child labour are a form of government concern for the protection of children's rights which aim to achieve justice, legal certainty and benefit for children. The provisions for these sanctions are regulated in Law Number 35 of 2014 concerning Child Protection.